Pellet analysis evidences flexibility in the diet of Brown Skua (Stercorarius antarcticus) during breeding at Esperanza/Hope Bay (Antarctic Peninsula) - Ibañez, Andres Esteban; Morales, Lara Mariel; Torres, D. S.; Borghello, P.; Montalti, Diego (Polar Biology)
At Esperanza/Hope Bay, Antarctic Peninsula, breeding Brown Skuas (Stercorarius antarcticus) coexist with a breeding colony of Adélie (Pygoscelis adeliae) and Gentoo (P. papua) penguins. Previously, we reported that the principal prey consumed by Brown Skuas was penguin, however, the contribution of marine resources to their diet was high. Besides, the number of conspecifics that compete for this resource gradually increases across the season. This prompted us to enquire into the ecological factors that may promote the use of marine resources during the breeding cycle. For this, during the 2014–2015 and 2015–2016 seasons, 400 regurgitated pellets were collected over the breeding season for different stages in the nesting cycle: incubation, early and late chick rearing. Prey items were classified according to different categories (penguin, fish, mollusk, and crustacea), and the occurrence frequency of each category was determined. As expected, penguins were the main prey consumed, but the occurrence of fish and mollusks increased for both early and late care of chicks. The flexibility in skua foraging behavior may be related to the changing degree of central place forager, and to the fluctuating energy requirements during each breeding stage. Moreover, the conspicuous decline in penguin availability or accessibility induced by intraspecific competition, may represent an alternative driving force in their foraging behavior over the breeding season. Fil: Ibañez, Andres Esteban. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Morales, Lara Mariel. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección Ornitología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; ...